Hydrogeologic behavior of an alluvial aquifer, Salta Province, Argentina: Simulations of hydraulic conductivity field, groundwater flow, and chloride migration - Köhn, Jacqueline (2002)
This work was designed to analyze the hydrogeological behavior of an alluvial aquifer in the River Mojotoro basin site in the Province of Salta, Argentina. The study area presents coarse-grained sediments with high infiltration capacity. The hydraulic conductivity field is affected by the physical heterogeneity of the medium and a geostatistical method, kriging, was used to construct this field from local measurements. The groundwater flow velocity field is computed using a hybrid mixed finite-element method and small variations in the flow directions were determined. Given the existence of a point source of chloride in the region under study, the spatial distribution of the generated plume in the saturated zone is analyzed. The advection-diffusion equation describing the transport of chloride in vertical and horizontal cross-sectional planes of the aquifer is discretized employing a method of characteristics combined with a mixed finite-element procedure, which provides an efficient method to eliminate spurious numerical oscillations and handle the convective term in the equation. The migration of chloride shows patterns, which are affected by the litologic heterogeneities of the aquifer and the regional groundwater flow.